Allograftinf in the case of revision hip arthroplasty at aseptic loosening of the acetabular component - Filipenko, Volodymyr; Vorontsov, Petro; Valeriia, Husak; Zorik, Arutunan; Samoylova, Kateryna; Slota, Oksana; Mezentsev, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Bone loss and significant acetabular defects remain one of the major problems in revision hip arthroplasty. A promising material for grafting of bone defects can be materials based on allogeneic bone after various types of processing, combining optimal properties for osteoregeneration. Objective. To analyze the results of acetabular reconstruction with bone implants «OMS-A» in the case of revision arthroplasty. Methods. The results of examination and treatment of 57 patients (33 women and 24 men) were analyzed. The patients’ age at the time of hospitalization ranged from 24 to 81 years. Patients were diagnosed on the basis of a combination of clinical manifestations of the disease, laboratory data, radiography, computed tomography with 3D reconstruction. According to the classification of W. G. Paprosky, the largest group consisted of type I defects — 25 patients (44 %), II — 13 (23 %), III — 19 (33 %). For the reconstruction of the acetabulum, 21 patients (37%) we used fragmented cortical-cancellous pieces (CGP), 28 (49 %) — volumetric bone implants (OCI), 8 (14 %) — a combination of CGP and OCI. All patients underwent revision hip arthroplasty with an anterolateral approach according to Harding. The resulting acetabular defect was tightly filled with an allografts. Results. X-ray and G. A. Gie results were assessed as good in 36 patients (63 %), satisfactory — in 14 (25 %). The manifestations of infection associated with the use of bone implants «OMS-A» have not been determined. The necessity for repeated surgery in order to restore the acetabulum occurred in 7 patients (12 %). Conclusions. Тhe clinical efficiency of bone implants «OMS-A» for the reconstruction of the acetabulum according to the classification of W. G. Paprosky was: with type I defect — 92 %; with type I and type defect — 92.3 %; with type II and type defect — 78.9 %.